The lion of Mars - Holm, Jennifer L. (Yearling, 2022)
Bell has spent his whole life in the U.S. colony on Mars, feeling alone and always being told it was dangerous to go outside their colony or to make contact with other settlements on Mars. Then, all the grown-ups get sick from a virus that has left Bell and the other kids untouched, forcing Bell and his friends to become courageous and venture outside to find the truth and save his family.